Comparison of shear ultrasonic results of electrolyte-acetamide molten mixtures - PŁOWIEC, R.; BERCHIESI, G. (Archives of Acoustics, 1994)
Shear ultrasonic investigation are presented in sodium trifluoroacetate/CF3COONa/-acetamide molten mixtures as a function of amide concentration. This results are compared with other electrolyte-acetamide molten mixtures investigated previously.